Magnesia and its manufacturing method, highly thermally conductive magnesia composition, and magnesia ceramics using the same
Patent Information
- Application Number
- JP2021521100
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-13
- Filing Date
- 2019-12-13
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2039-12-13
AI Technical Summary
【0021】 本発明によるマグネシアの製造方法は、熱処理中、MgOグラニュールの表面にグラニュールの内部とは異なる「MgOとドナー素材」を含む表面酸化物層が形成されることにより、MgOの低い耐吸湿性を改善させる効果がある。このようなマグネシアは、熱界面素材用セラミックフィラーに活用されうる。
Smart Images

Figure 0007638207000002 
Figure 0007638207000003 
Figure 0007638207000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnesia for ceramic filler that is used as a thermal interface material by forming a surface oxide layer containing MgO-donor different from that inside the granule on the surface of the MgO granule during heat treatment after adding a donor to MgO powder, and improving moisture absorption resistance, and a method for producing the same.The present invention also relates to a highly thermally conductive magnesia composition that lowers the sintering temperature and improves the thermal diffusion coefficient by adding a donor to MgO, and a magnesia ceramic using the same. [Background technology]
[0002] In manufacturing components such as high-output LEDs and power devices that consume high power and generate a lot of heat, heat dissipation packages are used to ensure the reliability and long life of the components.
[0003] Typically, a heat dissipation package is made up of a highly thermally conductive insulating substrate, a metal heat sink, A thermal interface material (TIM), which is a heat dissipation adhesive, is used between the highly thermally conductive insulating substrate and the metal heat sink.
[0004] Thermal interface materials can act as adhesives to bond highly thermally conductive insulating substrates and metal heat sinks together, or can be used alone as heat dissipation components. These thermal interface materials consist of a composite of a polymer and a highly thermally conductive metal or ceramic filler material.
[0005] Thermal interface materials are mainly polymers with Al 2 O 3 It is used by incorporating fillers.
[0006] But Al 2 O 3 The filler material has a rather low thermal conductivity of 20-30 W / mK, which needs to be improved.
[0007] On the other hand, the raw material cost of MgO is 2 O 3 The thermal conductivity is 30-60W / mK, which is equivalent to that of Al. 2 O 3 It has superior thermal conductivity compared to filler materials. 14 It has a resistivity of over ohm·cm and is excellent in electrical insulation. 2 O 3 When MgO filler is used instead of Al filler, 2 O 3 It is useful as a filler for TIM because it can improve the thermal conductivity of thermal interface materials based on
[0008] However, MgO has a relatively high hygroscopicity, and its thermal conductivity decreases when it absorbs moisture. Furthermore, Mg(OH) generated on the surface of MgO due to moisture absorption 2 This makes it difficult to combine with polymers, making it difficult to manufacture as a TIM, and is prone to problems such as the high possibility of separation from the polymer material due to volume expansion. This is an obstacle to the practical use of MgO as a thermally conductive ceramic filler. For this reason, in order to develop MgO as a thermally conductive ceramic filler for TIM, the development of technology that can improve moisture absorption resistance must be prioritized.
[0009] On the other hand, MgO is alumina (Al 2 O 3 ) it has the advantage of having a high thermal conductivity of 30-60W / mK.
[0010] However, alumina (Al 2 O 3 ) is sintered at about 1500~1600℃, whereas magnesia (MgO) has the disadvantage of being sintered at high temperatures of over 1700℃, so the sintering conditions for magnesia (MgO) need to be improved. Although there have been attempts to sinter magnesia (MgO) at low temperatures, there has been no research into heat-dissipating ceramic materials that can be sintered at lower temperatures while maintaining thermal conductivity.
[0011] Therefore, while maintaining the high thermal conductivity properties of magnesia (MgO), alumina (Al 2 O 3 There is a need for research and development of new, cost-competitive, low-cost oxide materials with high thermal conductivity that can be sintered at temperatures lower than 1500°C, the sintering temperature of conventional oxides. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] Korean Patent Publication No. 10-2016-0014590 (Published on February 11, 2016) Summary of the Invention [Problem to be solved by the invention]
[0013] An object of the present invention is to provide magnesia which has excellent moisture absorption resistance and can be applied to a ceramic filler for a thermal interface material, and a method for producing the same.
[0014] Another object of the present invention is to provide a magnesia (MgO) composition and a magnesia (MgO) ceramic which can ensure both low-temperature sintering (<1500° C.) and high thermal conductivity.
[0015] The object of the present invention is not limited to the object mentioned above, and other objects and advantages of the present invention not mentioned can be understood from the following description and can be more clearly understood from the embodiments of the present invention. Also, it is easy to understand that the object and advantages of the present invention can be realized by the means and combinations thereof described in the claims. [Means for solving the problem]
[0016] The present invention relates to a method for producing ... Mixed notes(d) forming donor-doped MgO granules from a mixture of the above-mentioned donor-doped MgO granules; and (d) heat-treating the donor-doped MgO granules, wherein the donor-doped MgO granules are heat-treated to form a surface oxide layer on the surface of the MgO granules, the composition of which is different from that of the interior of the MgO granules.
[0017] The present invention also provides a method for producing a ferroelectric material comprising the steps of: (a) Mg(OH) 2 (b) adding a donor and distilled water to the powder to form a mixture; (c) drying the mixture; Mixed notes From the mixture, the donor-added Mg(OH) 2 (d) forming granules; and (e) forming the donor-doped Mg(OH) 2 and heat treating the granules to obtain the donor-doped Mg(OH) 2 The present invention provides a method for producing magnesia (MgO) by heat-treating granules to form a surface oxide layer on the surface of the MgO granules, the composition of which is different from that of the interior of the MgO granules.
[0018] The present invention also provides magnesia (MgO), comprising: MgO granules; and a surface oxide layer formed on the surface of the MgO granules; wherein the composition of the surface oxide layer is different from the composition inside the MgO granules.
[0019] In addition, the present invention provides a method for forming a TiO 2 , Nb 2 O 5 , ZrO 2 Or Al 2 O 3 The magnesia (MgO) composition satisfies the following formula 1, 2, 3, or 4:
[0020] Formula 1 MgO+xwt.% TiO 2 , Formula 2 MgO+ywt.%Nb 2 O 5 Formula 3 MgO+zwt.%ZrO 2 Formula 4 MgO+wwt.%Al 2 O 3 (x, y, z, and w in the above formulas 1 to 4 are 0 <x、y、z、w≦10.0である。) Effect of the Invention
[0021] The method for producing magnesia according to the present invention has the effect of improving the low moisture absorption resistance of MgO by forming a surface oxide layer containing "MgO and donor material" on the surface of MgO granules during heat treatment, which is different from the inside of the granules. Such magnesia can be used as a ceramic filler for thermal interface materials.
[0022] The present invention also provides TiO 2 , Nb 2 O 5 , ZrO 2 , Ga 2 O 3 , Mn 2 O 3 , B 2 O 3 , Fe 2 O 3 , SnO 2 , MnO 2 , SiO 2 , V 2 O 5 , Ta 2 O 5 , Sb 2 O 5 , Y 2 O 3 ,EU 2 O 3 , Er 2 O 3 and Al 2 O 3 By adding a ceramic composition containing one or more of the above to magnesia (MgO), it is possible to sinter magnesia (MgO), which has high thermal conductivity, at a temperature lower than 1500°C, while the magnesia (MgO) material with an improved thermal diffusion coefficient can be used as a low-cost heat-dissipating ceramic material.
[0023] In addition to the above-mentioned effects, specific effects of the present invention will be described below together with specific matters for carrying out the invention. [Brief description of the drawings]
[0024] [Figure 1] 1 is a conceptual diagram of the formation of a dense surface oxide layer by heat treatment during the production of MgO granules of the present invention, and a photograph of the microstructure of the surface and inside of the sintered body. [Diagram 2] Photographs of the microstructure showing the shape and size of MgO granules produced according to the production method of the present invention, and photographs of the surface microstructure before and after heat treatment (1400°C, 2h). [Diagram 3] A photograph showing the difference in resistance to water reaction between MgO raw powder and MgO granules that have been heat-treated (1400°C, 2h) after adding a donor to the MgO powder. [Figure 4] Photographs of the fracture surface microstructures of a MgO+0.3wt.%TiO2+0.3wt.%Nb2O5+0.2wt.%SiO2 specimen (left) and a MgO+0.3wt.%TiO2+0.3wt.%Nb2O5 specimen (right) that were heat treated at 1400℃ for 2 hours, showing the thickness of the surface oxide layer. [Diagram 5] Energy Dispersive X-Ray Spectroscopy (EDS) analysis results and microstructure photographs confirming the formation of a surface oxide layer containing MgO-donors in a MgO+0.3wt.%TiO2+0.3wt.%Nb2O5+0.2wt.%SiO2 specimen heat-treated at 1400℃ for 2 hours. [Figure 6] 1 is a graph showing the change in thermal diffusivity of a specimen obtained by adding a TiO2 composition to magnesia (MgO) and sintering the same. [Figure 7] 1 is a graph showing the change in thermal diffusivity of a specimen obtained by adding a Nb2O5 composition to magnesia (MgO) and sintering the same. [Figure 8] 1 is a graph showing the change in thermal diffusivity and the change in density of a test piece obtained by adding a small amount of TiO2 (or Nb2O5) composition to magnesia (MgO) and sintering it. [Figure 9]1 is a graph showing the change in thermal diffusivity and the change in density of a test piece obtained by adding 0.3 wt. % TiO2 + a trace amount of Nb2O5 composition to magnesia (MgO) and sintering it. [Figure 10] 1 is a graph showing the change in thermal diffusivity of a specimen obtained by adding a ZrO2 composition to magnesia (MgO) and sintering the same. [Figure 11] 1 is a graph showing the change in thermal diffusivity of a specimen obtained by adding a 0.3 wt. % TiO2 + 0.3 wt. % Nb2O5 + ZrO2 composition to magnesia (MgO) and sintering the same. [Figure 12] 1 is a graph showing the change in thermal diffusivity of a specimen obtained by adding an Al2O3 composition to magnesia (MgO) and sintering the same. [Figure 13] 1 is a graph showing the change in thermal diffusivity and the change in density of a test piece obtained by adding a composition of 0.3 wt. % TiO2 + 0.3 wt. % Nb2O5 + a trace amount of Al2O3 to magnesia (MgO) and sintering it. [Figure 14] A specimen in which 2.0 wt.% TiO2 composition was added to magnesia (MgO), and a specimen in which 2.0 wt.% ZrO2 composition was added to magnesia (MgO) were sintered at 1400℃ for 2 hours, and then the fracture surface was observed with an electron microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] The above-mentioned objects, features and advantages will be described in detail below with reference to the accompanying drawings, so that those skilled in the art to which the present invention pertains can easily implement the technical idea of the present invention. In the description of the present invention, if a detailed description of a known technology according to the present invention is deemed to make the gist of the present invention unclear, the detailed description will be omitted. Hereinafter, a preferred embodiment of the present invention will be described in detail with reference to the accompanying drawings. The same reference numerals in the drawings are used to indicate the same or similar components.
[0026] Hereinafter, magnesia and its manufacturing method according to several embodiments of the present invention, a highly thermally conductive magnesia composition, and a magnesia ceramic using the same will be described.
[0027] The method for producing magnesia of the present invention includes the steps of adding a donor and an organic solvent to MgO powder to form a mixture, drying the mixture, and Mixed notes forming donor-doped MgO granules from the mixture; and heat treating the donor-doped MgO granules.
[0028] The donor-added MgO granules are then heat-treated to form a surface oxide layer on the surface of the MgO granules, the surface oxide layer having a composition different from that of the interior of the MgO granules.
[0029] The donor in the present invention means a metal oxide having a higher metal valence than MgO, that is, an oxide having a valence of three or more.
[0030] On the other hand, the method for producing magnesia of the present invention uses Mg(OH) instead of the MgO powder. 2 Mg(OH) is used. 2 When linear shrinkage is used, the shrinkage rate of the sintered body and granules after heat treatment (linear shrinkage rate) The shrinkage is shown to be 20 to 40%. This shrinkage rate is significantly different from the 10 to 30% shrinkage rate when MgO is used.
[0031] Mg(OH) instead of MgO powder 2 When producing magnesia using powder as a starting material, it is preferable to add distilled water instead of an organic solvent. In the conditions for the method for producing magnesia using MgO powder described later, the starting material Mg(OH) 2 Magnesia can be produced under the same conditions, except that ethyl acetate and distilled water are used.
[0032] The manufacturing method below will be described as a method for producing magnesia using MgO powder.
[0033] In the step of adding the donor and the organic solvent to the MgO powder to form a mixture, the mixture may be formed by mixing the MgO powder with a solution prepared by dissolving and dispersing the donor in the organic solvent.
[0034] The total of the MgO powder and the donor was 100 wt.% TiO 2 , Nb 2 O 5 , ZrO 2 , Ga 2 O 3 , Mn 2 O 3 , B 2 O 3 , Fe 2 O 3 , SnO 2 , MnO 2 , SiO 2 , V 2 O 5 , Ta 2 O 5 , Sb 2 O 5 , Y 2 O 3 ,EU 2 O 3 , Er 2 O 3 and Al 2 O 3 A small amount of 0.01 to 10.0 wt.% of a donor containing one or more of the above is added.
[0035] If the amount of the donor added is outside this range, it may be difficult for the magnesia to maintain its moisture absorption resistance and thermal conductivity properties as a ceramic filler for a thermal interface material.
[0036] The donor and organic solvent are added to the MgO powder, and then mixed and crushed by ball milling to form a mixture.
[0037] In the step of forming the mixture, milling may be carried out for 0.5 to 72 hours.
[0038] If the grinding time is too short, less than 0.5 hours, the mixing and grinding effect of MgO and the donor additive may be insufficient, whereas if it exceeds 72 hours, the grinding time is too long and the process may be inefficient.
[0039] The organic solvent may be 2-propanol, absolute alcohol, or distilled water. When distilled water is used, Mg(OH) 2 The shrinkage rate is 20 to 40% due to the formation of 2-propanol or absolute alcohol. This shrinkage rate is significantly different from the shrinkage rate of 10 to 30% for sintered bodies and granules after heat treatment when 2-propanol or absolute alcohol is used.
[0040] The step of drying the mixture is carried out to remove the organic solvent, which can be removed by natural drying at 25±5° C. or by drying at 25° C. or higher.
[0041] before Mixed notes In the step of forming the donor-doped MgO granules from the mixture, various methods can be used to form the MgO granules from the MgO powder.
[0042] For example, by rotating a cylindrical container at a rotation speed of 10 to 500 rpm, MgO granules of various sizes can be formed from MgO powder, and MgO granules to which a donor is added can also be formed.Comparing the difference between the powder and the granules, the particle size of the granules is larger than that of the powder.
[0043] The donor-added MgO granules can be prepared by the same method as the above-mentioned method for forming MgO granules, and the donor-added MgO granules can be prepared in a form in which the donor is dispersed on the surface of the MgO granules.
[0044] The step of heat treating the donor-doped MgO granules may be performed at 800 to 1800°C.
[0045] During the heat treatment, some of the donors are transferred to the surface of the granules and form a surface oxide layer containing MgO and the donors, so that a surface oxide layer containing MgO-donors is formed on the surface of the MgO granules during the heat treatment step.
[0046] The heat treatment is preferably performed at a temperature of 800 to 1800° C., and if the temperature is outside this range, an oxide layer may not be sufficiently formed as a surface protective layer on the surface of the MgO granules.
[0047] As in the previous preparation method, Mg(OH) 2 When producing magnesia using powder as the starting material, Mg(OH) 2 adding a donor and distilled water to the powder to form a mixture; drying the mixture; Mixed notes From the mixture, the donor-added Mg(OH) 2 Forming granules and doping the donor Mg(OH) 2 and heat treating the granules to produce magnesia. The donor and heat treatment are as described above.
[0048] FIG. 1 shows the MgO granules produced by heat treatment during the production of the present invention. The dense Surface Oxidation layer Conceptual diagram of the formation of the surface and Sintered body This is a photograph of the internal microstructure.
[0049] As shown in Figure 1, some donors during the heat treatment process move along the grain boundaries and gather on the surface of the granules. The inside of the MgO granule is different from the inside. A dense, finely structured surface oxide layer is formed, A surface oxide layer is formed on the surface of the granules, the composition of which is different from that of the interior of the MgO granules.
[0050] In the present invention, the low moisture absorption resistance of MgO can be improved by the formation of a surface oxide layer.
[0051] Thus, in the present invention, MgO powder raw material or Mg(OH)2 Using powder raw materials, donor-added MgO granules or Mg(OH) 2 After forming the granules, the granules are heat-treated to produce magnesia, which forms a protective surface oxide layer containing MgO and donors on the surface of the MgO granules, ensuring moisture absorption resistance and excellent thermal properties.
[0052] For example, Mg and Mg containing one or more metal elements 2 TiO 4 , Zr 0.9 04 Mg 0.096 O 1.904 The surface oxide layer containing metal oxides such as ZnO, ZnO, and ZnO has the effect of improving the moisture absorption resistance of MgO by taking advantage of the free point in the moisture absorption problem.
[0053] The MgO powder raw material or Mg(OH) of the present invention 2 Magnesia produced from powder raw materials includes MgO granules and a surface oxide layer formed on the surface of the MgO granules, wherein the magnesia is characterized in that the composition of the surface oxide layer is different from the composition inside the MgO granules, and the surface oxide layer includes MgO and a donor.
[0054] The microstructure of the surface oxide layer is denser than the internal microstructure of the MgO granules. be.
[0055] The donor is a metal oxide having a higher metal valence than MgO, such as TiO 2 , Nb 2 O 5 , ZrO 2 , Ga 2 O 3 , Mn 2 O 3 , B 2 O 3 , Fe 2 O 3 , SnO 2 , MnO 2 , SiO 2 , V 2 O 5 , Ta 2 O5 , Sb 2 O 5 , Y 2 O 3 ,EU 2 O 3 , Er 2 O 3 and Al 2 O 3 Contains one or more of the following.
[0056] The donor (metal oxide) material may be contained in an amount of 0.01 to 10.0 wt.%, preferably 0.01 to 2.0 wt.%, relative to 100 wt.% of the total magnesia.
[0057] Specifically, the magnesia (MgO) is TiO 2 and Nb 2 O 5 and satisfies the following formula 6.
[0058] Formula 6 MgO + xwt.% TiO 2 +ywt.%Nb 2 O 5 ≦100wt.%
[0059] In the above formula 6, x and y are 0 <x、y≦2.0であ The remainder is MgO. do.
[0060] FIG. 2 is a photograph of the microstructure showing the shape and size of MgO granules produced according to the production method of the present invention, and a photograph of the surface microstructure before and after heat treatment (1400° C., 2 h).
[0061] As shown in Figure 2, the size of the sintered material varies depending on the manufacturing conditions (rpm). and shape The MgO granules can be produced by the heat treatment. Compared with the MgO granules before the heat treatment, the surface oxide layer of the MgO granules exhibits a dense microstructure after the heat treatment.
[0062] The microstructure of the surface oxide layer is denser than the internal microstructure of the MgO granules. be.
[0063] FIG. 3 is a photograph showing the difference in resistance to water reaction between MgO raw material powder and MgO granules that have been heat-treated (1400°C, 2 hours) after adding a donor to the MgO powder.
[0064] The MgO raw powder is a powder to which no donor is added. When it is kept in an environment of 85°C and 85% humidity for 72 hours, Mg(OH) 2 was observed.
[0065] Meanwhile, granules prepared from donor-doped MgO powder according to the manufacturing method of the present invention and heat-treated at 1400°C showed no Mg(OH) formation on the surface of the granules when kept in an environment of 85°C and 85% humidity for 72 hours. 2 has not been observed.
[0066] These results indicate that when a donor is added to the MgO powder raw material to form MgO granules and then heat-treated as in the present invention, the granules do not react with water and the moisture absorption resistance is improved.
[0067] Figure 4 shows MgO+0.3wt.%TiO heat-treated at 1400℃ for 2 hours. 2 +0.3wt.%Nb 2 O 5 +0.2wt.%SiO 2 Specimen (left) and MgO+0.3wt.%TiO 2 +0.3wt.%Nb 2 O 5 This is a microscopic photograph of the fracture surface of the specimen (right side), which shows the thickness of the surface oxide layer.
[0068] The donor-added MgO formed a surface oxide layer that was separated from the inside of the specimen (granule) after heat treatment. MgO+0.3wt.%TiO 2 +0.3wt.%Nb 2 O 5 +0.2wt.%SiO 2 It can be seen that a surface oxide layer of 0.1μm to 3μm thick containing MgO-donor was formed on the specimen. MgO + 0.3wt.% TiO 2 +0.3wt.%Nb2 O 5 TEM images of the specimens also show a surface oxide layer thinner than 0.1 μm.
[0069] Figure 5 shows the MgO+0.3wt.%TiO heat treated at 1400℃ for 2 hours. 2 +0.3wt.%Nb 2 O 5 +0.2wt.%SiO 2 The formation of a surface oxide layer containing MgO-donors can be confirmed on the specimen. These are the results of Dispersive X-Ray Spectroscopy (EDS) analysis and a photograph of the microstructure.
[0070] When the donor-doped MgO was heat-treated, a surface oxide layer of a different phase from the interior was formed.
[0071] It was confirmed that the MgO content was higher inside the sintered specimen than on the surface, which means that a surface oxide layer containing MgO-donors was formed on the surface of the sintered body.
[0072] The donor content in the surface oxide layer was higher than that in the MgO granules. This indicates that the donor was added at 2.0 wt.% or less for 100 wt.% magnesia, and the donor concentration in the surface oxide layer was higher than the average donor concentration in the whole (granules and surface oxide), and therefore the donor content in the surface oxide layer was higher than that in the granules. The difference was measured to be at least 2 times, preferably 3 times, and more preferably 10 times higher than the donor content in the granules.
[0073] The highly thermally conductive magnesia (MgO) composition of the present invention has TiO in the MgO matrix. 2 , Nb 2 O 5 , ZrO 2 Or Al 2 O 3It includes and satisfies the following Formula 1, Formula 2, Formula 3 or Formula 4.
[0074] Formula 1: MgO + xwt.%TiO 2 ≦100wt.% Formula 2: MgO + ywt.%Nb 2 O 5 ≦100wt.% Formula 3: MgO + zwt.%ZrO 2 ≦100wt.% Formula 4: MgO + wwt.%Al 2 O 3 ≦100wt.%
[0075] above In Formulas 1 to 4, x, y, z, and w satisfy 0 < x, y, z, w ≤ 10.0 And the remaining Part is MgO That is 。
[0076] Preferably, in Formula 1, x satisfies 0 < x ≤ 10.0, in Formula 2, y satisfies 0 < y ≤ 5.0, in Formula 3, z satisfies 0 < z ≤ 4.0, and in Formula 4, w may satisfy 0 < w ≤ 0.8. More preferably, in Formula 2, y may satisfy the range of 0 < y ≤ 1.0.
[0077] Referring to FIG. 6 and Table 1, it can be seen that when TiO ( 2 ) is added as a donor to the magnesia (MgO) in an amount exceeding 0 wt.% to 10.0 wt.% or less, the thermal diffusivity of the magnesia (MgO) ceramics according to the present invention increases.
[0078] In particular, referring to FIGS. 6, 8 and Table 1, it can be seen that when TiO ( 2 ) is added as a donor to the magnesia (MgO) in an amount exceeding 0 wt.% to 2.0 wt.% or less and sintered at 1400 °C, it is similar to or more excellent than the thermal diffusivity of the magnesia (MgO) ceramics sintered at 1700 °C.
[0079] Also, referring to FIG. 6, FIG. 8 and Table 1, the titanium dioxide (TiO 2 ) when added at more than 0 wt.% but not exceeding 10.0 wt.% and sintered at 1300°C to 1400°C, it was confirmed that it exhibited a high relative density of 96% or more for all compositions, which is a significant improvement over the relative density of 80-90% for magnesia (MgO) ceramics sintered at the same sintering temperature.
[0080] In addition, the magnesia (MgO) sintered at a low temperature of 1300°C to 1400°C contains 0 wt.% to 10.0 wt.% titanium dioxide (TiO 2 It can be seen that the thermal diffusivity of the composition to which SiO2 is added is higher than that of magnesia (MgO) sintered at the same sintering temperature.
[0081] 7 and 8, the niobium pentoxide (Nb 2 O 5 When 0 wt.% to 5.0 wt.% is added, the thermal diffusivity of the magnesia (MgO) ceramics according to the present invention sintered at 1300°C to 1400°C is similar to or better than that of the magnesia (MgO) ceramics sintered at 1700°C.
[0082] In particular, referring to FIG. 7 and FIG. 8, the niobium pentoxide (Nb 2 O 5 When 1.0 wt.% or less of MgO is added, the thermal diffusivity of the specimen sintered at 1400°C is superior to that of the magnesia (MgO) ceramic sintered at 1700°C.
[0083] In Figure 9, 0.3 wt.% TiO 2 is fixed, and Nb 2 O 5 It can be confirmed that by further adding 1.0 wt.%, an improvement in the thermal conductivity properties is observed.
[0084] Referring to FIG. 10, the zirconium oxide (ZrO 2 When 0 wt.% to 4.0 wt.% is added, the thermal diffusivity of the magnesia (MgO) ceramics according to the present invention sintered at 1400°C is similar to that of the magnesia (MgO) ceramics sintered at 1700°C.
[0085] Referring to FIG. 11, the titanium dioxide (TiO 2 ), niobium pentoxide (Nb 2 O 5 ) and the zirconium oxide (ZrO 2 Even when both are added, the thermal diffusivity of the specimens sintered at 1300°C to 1400°C is similar to or better than that of magnesia (MgO) ceramics sintered at 1700°C.
[0086] In particular, referring to FIG. 11, the titanium dioxide (TiO 2 ) 0.3wt.%, the niobium pentoxide (Nb 2 O 5 ) 0.3 wt.% and the zirconium oxide (ZrO 2 ) is added in an amount of more than 0 wt.% and not more than 0.05 wt.%, the thermal diffusivity of the magnesia (MgO) ceramic according to the present invention is significantly higher than that of the magnesia (MgO) ceramic sintered at 1700°C.
[0087] Referring to FIG. 12, the magnesia (MgO) is added as a donor to the alumina (Al 2 O 3 It can be seen that when more than 0 wt.% and 0.8 wt.% or less is added, the thermal diffusivity of the magnesia (MgO) ceramic according to the present invention increases.
[0088] In Figure 13, 0.3 wt.% TiO 2 and 0.3wt.% Nb 2 O 5 and Al2 O 3 Further addition of did not significantly decrease the thermal conductivity properties, and showed a similar tendency in the thermal conductivity properties.
[0089] The highly thermally conductive magnesia (MgO) composition of the present invention has TiO in the MgO matrix. 2 , Nb 2 O 5 and ZrO 2 and satisfies the following formula 5.
[0090] Formula 5 MgO + 0.3wt.% TiO 2 +0.3wt.%Nb 2 O 5 +zwt.%ZrO 2 ≦100wt.%
[0091] In the above formula 5, z is 0 <z≦0.05であ The remainder is MgO. do.
[0092] As described above, referring to Figs. 6 to 13 and Table 1, TiO with a valence of 3 or more that can act as a donor to MgO is 2 , Nb 2 O 5 , ZrO 2 , Ga 2 O 3 , Mn 2 O 3 , B 2 O 3 , Fe 2 O 3 , SnO 2 , MnO 2 , SiO 2 , V 2 O 5 , Ta 2 O 5 , Sb 2 O 5 , Y 2 O 3 ,EU 2 O 3 , Er 2 O 3 and Al 2 O 3The samples with small amounts of one or more of the metal oxide compositions added show improved thermal properties compared to the samples with no donor added to MgO.
[0093] The method for producing magnesia ceramics of the present invention includes the steps of adding and mixing a donor to magnesia (MgO) to produce any of the high thermal conductivity magnesia (MgO) compositions, drying the composition, and sintering the composition. The sintering can be performed at 1200°C to 1500°C.
[0094] In low-temperature sintering of magnesia (MgO), low-temperature sintering can be achieved by adding one or more substances that can act as donors, which improves the sinterability.
[0095] The donor is TiO 2 , Nb 2 O 5 , ZrO 2 , Ga 2 O 3 , Mn 2 O 3 , Fe 2 O 3 , SnO 2 , MnO 2 , SiO 2 , V 2 O 5 , Ta 2 O 4 , Sb 2 O 5 , Y 2 O 3 ,EU 2 O 3 , Er 2 O 3 and Al 2 O 3 Contains one or more of the following.
[0096] The magnesia (MgO) ceramics of the present invention is made by adding titanium dioxide (TiO) to magnesia (MgO) as a donor. 2 ), Niobium pentoxide (Nb 2 O 5 ), zirconium oxide (ZrO2 ) and / or alumina (Al 2 O 3 ) is added and mixed in a ball mill using 2-propanol as a solvent, then crushed and dried. . Mixed The composite powder is molded in a circular metal mold with a diameter of 15 mm at a pressure of 100 MPa, and then sintered in an electric furnace or gas furnace at a temperature of 1200°C to 1500°C for two hours to produce the composite powder.
[0097] The high thermal conductivity magnesia (MgO) ceramics produced by the production method of the present invention has a theoretical density of magnesia (MgO) (3.58 g / cm 3 ) can exhibit relative density values of 93% to 100%. Or, when a donor element heavier than Mg is added, 3.58 g / cm 3 High thermal conductivity magnesia (MgO) ceramics can exhibit densities greater than 10.4 mm. 2 / s~21.9mm 2 It can exhibit a thermal diffusivity value of 100 / s.
[0098] Figure 14 shows the results of the 2.0 wt.% TiO 2 A specimen with the composition added and a specimen with 2.0wt.% ZrO in magnesia (MgO) 2 Photographs of the microstructures of the fracture surfaces of a test piece with and without the composition added were observed with an electron microscope after sintering at 1400°C for 2 hours.
[0099] Referring to FIG. 14, when sintered at 1400° C., it shows a very dense microstructure.
[0100] Thus, specific examples of magnesia, its manufacturing method, highly thermally conductive magnesia composition, and magnesia ceramics using the same are as follows.
[0101] 1. Density The measurement was performed by the Archimedes method using xylene.
[0102] 2. Thermal diffusivity The measurements were taken using the laser flash method. (LFA 457,MicroFlash,Netzsch Instruments Inc.,Germany)
[0103] Table 1 shows the density and thermal diffusivity properties of sintered specimens of magnesia (MgO) compositions in the temperature range provided by the present invention.
[0104] [Table 1]
[0105] Example 1: Magnesia (MgO) containing 0.5 wt.% titanium dioxide (TiO) as a donor 2 ) is added and mixed in a ball mill using 2-propanol as a solvent, and then these are crushed and dried.
[0106] The dried mixed powder is molded in a circular metal mold with a diameter of 15 mm at a pressure of 100 MPa, and then sintered in an electric furnace at a temperature of 1300° C. for 2 hours.
[0107] Examples 2 to 32: Magnesia (MgO) of Example 1 was used with titanium dioxide (TiO) as a donor. 2 ), Niobium pentoxide (Nb 2 O 5 ), zirconium oxide (ZrO 2 ), Alumina (Al 2 O 3 ), V 2 O 5 , B 2 O 3 , Y 2 O 3 , SiO 2 ,EU 2 O 3 , Er 2 O 3 , Fe 2 O 3The high thermal conductive magnesia ceramics were manufactured in the same manner as in Example 1, except that the above were added in the amounts shown in Table 1 and sintered at a temperature of 1300°C or 1400°C.
[0108] Comparative Example 1: Magnesia ceramics were manufactured in the same manner as in Example 1, except that the donor was not added to the magnesia (MgO) in Example 1.
[0109] Comparative Example 2: Magnesia ceramics were manufactured in the same manner as in Example 1, except that no donor was added to the magnesia (MgO) in Example 1 and the magnesia (MgO) was sintered at a temperature of 1400°C.
[0110] Comparative Example 3: Magnesia ceramics were manufactured in the same manner as in Example 1, except that no donor was added to the magnesia (MgO) in Example 1 and the magnesia (MgO) was sintered at a temperature of 1700°C.
[0111] Referring to Table 1 above, it can be seen that the magnesia (MgO) composition is sufficiently sintered in the temperature range of 1300°C to 1400°C, and that the density and thermal diffusivity of the magnesia (MgO) ceramics change depending on the donor composition ratio.
[0112] Specifically, referring to Examples 1 to 32, the titanium dioxide (TiO 2 ), Niobium pentoxide (Nb 2 O 5 ), zirconium oxide (ZrO 2 ), Alumina (Al 2 O 3 ), V 2 O 5 , B 2 O 3 , Y 2 O 3 , SiO 2 ,EU 2 O 3 , Er 2 O 3 and Fe2 O 3 When one or more of the above are added, the magnesia (MgO) ceramics according to the present invention has a density of 3.02 g / cm 3 ~3.59g / cm 3 It was found that the sintered material showed an excellent density value of 10.4 mm. 2 / s~21.9mm 2 It can be seen that the material exhibits an excellent thermal diffusivity value of 0.1% by mass / s.
[0113] As described above, the high thermal conductive magnesia (MgO) ceramics manufactured by the manufacturing method of the present invention exhibits a high sintering density value compared to conventional magnesia (MgO) ceramics. Therefore, the high thermal conductive magnesia (MgO) ceramics manufactured by the manufacturing method of the present invention exhibits a high thermal diffusivity value compared to conventional magnesia (MgO) ceramics, and can be applied to heat dissipation ceramic materials.
[0114] As described above, the present invention has been described with reference to the drawings illustrating the present invention, but the present invention is not limited to the embodiments and drawings disclosed in this specification, and it is obvious that various modifications can be made by those of ordinary skill in the art within the scope of the technical concept of the present invention. Furthermore, even if the effects of the configuration of the present invention have not been explicitly described in the above description of the embodiments of the present invention, it goes without saying that the effects that can be predicted by the configuration should also be recognized.
Claims
1. (a) adding a donor and an organic solvent to MgO powder to form a mixture; (b) forming donor-doped MgO granules from the mixture; and (c) a step of heat treating the MgO granules to which the donor has been added; wherein in the step (a), the donor is added in an amount of more than 0 wt % and not more than 2.0 wt % relative to a total amount of the MgO powder and the donor of 100 wt %, A method for producing magnesia (MgO) comprising the steps of: subjecting the MgO granules to the donor addition; forming a surface oxide layer on the surface; and making the surface oxide layer have a component composition different from that of the interior of the MgO granules; and making the donor content in the surface oxide layer higher than that of the interior of the MgO granules. The donor herein means a metal oxide having a higher metal valence than MgO, that is, an oxide of a metal having a valence of three or more.
2. (a) Mg(OH) 2 adding a donor and distilled water to the powder to form a mixture; (b) removing the donor-added Mg(OH) from the mixture; 2 forming granules; and (c) Mg(OH) to which the donor has been added 2 A method for producing magnesia (MgO), comprising the steps of: heat treating the granules; and, in the step (a), Mg(OH) 2 A method for producing magnesia (MgO) comprising the steps of: adding a donor in an amount of more than 0 wt% and not more than 2.0 wt% relative to a total amount of 100 wt% of powder and donor; heat-treating Mg(OH)2 granules to which the donor has been added; forming a surface oxide layer on the surface of the MgO granules, the composition of which is different from that of the interior of the MgO granules; and making the donor content in the surface oxide layer higher than that in the MgO granules. The donor herein means a metal oxide having a higher metal valence than MgO, that is, an oxide of a metal having a valence of three or more.
3. The donor is TiO 2 , Nb 2 O 5 , ZrO 2 , Ga 2 O 3 , Mn 2 O 3 , B 2 O 3 , Fe 2 O 3 , SnO 2 , MnO 2 , SiO 2 , V 2 O 5 , Ta 2 O 5 , Sb 2 O 5 , Y 2 O 3 , Eu 2 O 3 , Er 2 O 3 and Al 2 O 3 Including one or more of the following: A method for producing magnesia (MgO) according to claim 1 or 2.
4. In the step (c), the heat treatment is performed at 800 to 1800°C. A method for producing magnesia (MgO) according to any one of claims 1 to 3.
5. MgO granules; and a surface oxide layer formed on the surface of the MgO granules; The composition of the surface oxide layer and the composition inside the MgO granule are different from each other, the total of which is 100 wt % and the magnesia (MgO) contains a donor in an amount of more than 0 wt % and not more than 2 wt %. The donor content inside the surface oxide layer is higher than the donor content inside the MgO granule. The donor herein means a metal oxide having a higher metal valence than MgO, that is, an oxide of a metal having a valence of three or more.
6. MgO granules; and a surface oxide layer formed on the surface of the MgO granules; The density of the surface oxide layer is higher than the density inside the MgO granules, the magnesia (MgO) contains a donor in an amount of more than 0 wt% and not more than 2 wt%, taking the total as 100 wt%, and the donor content inside the surface oxide layer is higher than the donor content inside the MgO granules. The donor herein means a metal oxide having a higher metal valence than MgO, that is, an oxide of a metal having a valence of three or more.
7. The donor is TiO 2 , Nb 2 O 5 , ZrO 2 , Ga 2 O 3 , Mn 2 O 3 , B 2 O 3 , Fe 2 O 3 , SnO 2 , MnO 2 , SiO 2 , V 2 O 5 , Ta 2 O 5 , Sb 2 O 5 , Y 2 O 3 , Eu 2 O 3 , Er 2 O 3 and Al 2 O 3 Including one or more of the following:
7. Magnesia (MgO) according to claim 5 or 6.
Citation Information
Patent Citations
Highly heat conductive magnesia based powder
JP1988307107A
Insulation base plate
JP1989019606A
Corrosion resistant magnesia-based sintered compact, member for heat treatment formed from the same, and method for producing the sintered compact
JP2007284314A
Magnesium hydroxide particle having slow growth late and low aspect ratio method for producing the same
JP2017122029A
Sintered ceramic component and method of forming same
JP2018501178A